2019
DOI: 10.1002/elan.201900201
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic Activity of Ni‐CNT Nanocomposites for Simultaneous Determination of Epinephrine and Dopamine

Abstract: A promising electrochemical sensor based nickel‐carbon nanotube (Ni‐CNT) modified on glassy carbon (GC) electrode had been developed and the properties of the modified electrode were characterized by multispectroscopic analysis. The fabricated sensor (GC/Ni‐CNT) electrode was utilized to determine the catecholamines such as epinephrine and dopamine simultaneously. Differential pulse voltammetry and amperometry were used to verify the electrochemical behavior of the studied compounds. The GC/Ni‐CNT based ampero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Calculated based on the signal-tonoise ratio (S/N = 3), the limit of detection (LOD) values for DA and EP on the Ce-MoS 2 NFs/SPE biosensors were determined to be ~28 and 44 nM, respectively. When compared with recently reported DA and EP sensors, it becomes evident that the Ce-MoS 2 NFs/SPE biosensors exhibited the highest level of sensitivity in the simultaneous detection of DA and EP (Table S1) [3,13,[35][36][37][38][39][40][41]. The developed biosensors also showed high selectivity toward target DA and EP, while possible interfering molecules did not yield any considerable signal (Figure 6d).…”
Section: Enhanced Electrocatalytic Performance Of Ce-mos 2 Nfsmentioning
confidence: 69%
“…Calculated based on the signal-tonoise ratio (S/N = 3), the limit of detection (LOD) values for DA and EP on the Ce-MoS 2 NFs/SPE biosensors were determined to be ~28 and 44 nM, respectively. When compared with recently reported DA and EP sensors, it becomes evident that the Ce-MoS 2 NFs/SPE biosensors exhibited the highest level of sensitivity in the simultaneous detection of DA and EP (Table S1) [3,13,[35][36][37][38][39][40][41]. The developed biosensors also showed high selectivity toward target DA and EP, while possible interfering molecules did not yield any considerable signal (Figure 6d).…”
Section: Enhanced Electrocatalytic Performance Of Ce-mos 2 Nfsmentioning
confidence: 69%
“…Conversely, lack of selectivity may be advantageous if a summed determination of catecholamines is preferred. Notably, some recent studies showed simultaneous and selective electrochemical detection of individual catecholamines in biological fluids by using a combination of nanomaterial modifications (Fatma et al., 2019; Manivel et al., 2019; Vinoth et al., 2019). Fatma et al .…”
Section: Tailored Biosensing Strategiesmentioning
confidence: 99%
“…Conversely, lack of selectivity may be advantageous if a summed determination of catecholamines is preferred. Notably, some recent studies showed simultaneous and selective electrochemical detection of individual catecholamines in biological fluids by using a combination of nanomaterial modifications (Fatma et al, 2019;Manivel et al, 2019;Vinoth et al, 2019). Fatma et al reported excellent LODs (0.06 ppb and 0.02 ppb) for simultaneous dopamine and adrenaline detection in urine and showed that noradrenaline did not cause significant interference (Fatma et al, 2019).…”
Section: Electrochemical Detection Of Catecholaminesmentioning
confidence: 99%
“…As a significant sensor parameter, the sensitivity of NiOÀ ERGO/SPE was also determined to be 0.0806 μAμM À 1 for the detection of EPI by utilizing the slope of the calibration graph. To compare the detection performance of the proposed sensor, the analytical characteristics of both NiOÀ ERGO/SPE and EPI sensing studies in the last few years [3,5,[38][39][40][41][42][43][44] for EPI detection are summarized in Table 1. The results clearly show NiOÀ ERGO/SPE is comparable or better than EPI sensors reported in previous studies.…”
Section: Analytical Performancementioning
confidence: 99%